Method of Calculating Lake Water Storage in Areas without Topographical Data Based on Google Earth Engine. Issue 1 (February 2021) - Sun, Jiajun; Cui, Yingjie; Cao, Hongbin
Abstract: Accurate ecological lake water calculation plays an important role in maintaining ecological health of and protecting lakes. However, the lack of topographical data for the bottom of the lake results in some complexity to the calculation of ecological lake water storage. This study uses remote sensing big data to overcome the data limitations of water calculations and accurately calculates the ecological water storage of Baiyangdian Lake. The results show that the water surface area of Baiyangdian Lake can be divided into a dry period (average water area of 7.15 km 2 ), a decline period (155.64 km 2 ), a stable period (67.29 km 2 ), and a recovery period (119.17 km 2 ). The ecological water storage of the lake has evolved from 200 million m 3 to the current 300–600 million m 3 . This study provides an important reference for the ecological lake water calculations when topographical data is not available and for lakes with complex bottom topography.